An Appraisal of the Application of the Principle of Complementarity in the Functioning of the African Commission on Human and Peoples’ Rights and the African Court on Human and Peoples’ Rights Within the African Human Rights System - Mokake, Fritz Lifoko (Law and Economy, 2025)
The principle of complementarity is a very vital principle in international law. The principle of complementarity promotes respect for national sovereignty, encourages domestic accountability, prevents impunity, ensures efficient allocation of resources, and strengthens international-domestic cooperation. This article examines or makes an appraisal on the application of the principle of complementarity in the functioning of the African Human Rights Commission and the African Human Rights Court system. The study uses a qualitative research methodology, employing primary data sources from vital conventions like the Rome Statute, African Charter on Human and Peoples’ Rights, and a host of others. Secondary data came from textbooks, journal articles, reports, and newspapers. The study is underpinned or anchored by the natural law theory and the functional theory. The findings in the study reveals blatantly like that the principle of complementarity is crucial to the African human rights system, fostering a cooperative and mutually reinforcing relationship between the Commission and the Court but however, its effectiveness in practice has been characterized by variability, with both successful instances and significant challenges. And as result of this, there is need to enhance cooperation between the commission and the court, increase awareness and visibility, develop clear guidelines and to improve access to the court.